Antidepressants: current concepts of mode of action. - Cowen, P (1990)
Repeated administration of antidepressant drugs to rodents produces adaptive changes in noradrenaline and 5-hydroxytryptamine pathways in the brain. A decrease in cortical beta-adrenoceptor binding is seen following most antidepressant treatments and is thought by some to be of importance in the therapeutic action of antidepressants; however, it seems equally plausible that this change simply reflects a homeostatic response to increased noradrenergic transmission. Another effect common to many different antidepressant treatments is an increase in neurotransmission through post-synaptic 5-HT1 receptors in some brain regions. 5-HT neuroendocrine studies suggest that this change also occurs in the human brain. Further investigations are required to assess whether alterations in 5-HT neurotransmissions are important in the therapeutic action of antidepressant treatment.